For “a meaning-centered, culturally oriented psychology” of climate change - Reho, Matteo (Rivista di Psicologia Clinica - Open Access, 2025)
The present paper emphasizes the central role of meaning in human action, highlighting how the analysis of its emergence and reproduction can offer insights into complex phenomena, including the challenges posed by contemporary society, with a particular focus on the climate crisis. A micro-genetic model of the constitution of experience is initially proposed, followed by a presentation of the concept of “value of life” of signs. Next, the article introduces the Semiotic-Cultural Psychology Theory (SCPT), highlighting its processual interpretation of culture understood as a continuous sensemaking process. Two empirical studies are presented that apply the theoretical framework of SCPT, demonstrating the impact of meaning systems on pro-environmental behaviors: the first explores the relationship between wildfire risk perception and preventive behaviors and the moderating role played by symbolic universes, while the second analyzes the role of affect in the link between attitudes and pro-environmental behaviors. The results underscore the crucial importance of the symbolic universes and lines of semiotic force in shaping individuals’ perceptions, thoughts, and actions, suggesting relevant theoretical and practical implications for promoting a culture of sustainability.